An Improved GC Method forRapid Analysis of Valproic Acid in Human Plasma Without Derivatization: Determination of valproic acid in plasma - Ahmadkhaniha, Reza; Rastkari, Noushin; Kobarfard, Farzad; Pakdaman, Hossein; Ahmadkhaniha, Omid; Kebriaeezadeh, Abbas (Iranian Journal of Pharmaceutical Sciences, 2007)
Asimple, reproducible and rapid gas chromatographic method for precisedetermination of valproic acid (VPA) in human plasma has been developed. Totaltime for sample preparation and GC analysis is less than 45 min. After plasma proteinprecipitation, VPAwas extracted into chloroform with suitable recovery. By usingStabilwax®-DAcapillary GC column, a symmetrical gas chromatographic peak wasobtained without the need for derivatization. The calibration curve was proved tobe linear (r2 = 0.998) in a wide concentration range (0.45-100 μg/ml). Inter-day andintra-day accuracy and precision of this method was investigated during the methodvalidation and the method has good precision and accuracy. This method is highlyreproducible with a limit of detection 150 ng/ml of VPAin human plasma and couldbe used in TDM and pharmacokinetic studies.